2011
DOI: 10.5539/ijb.v4n1p27
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genome Sequence of Freshwater Araphid Pennate Diatom Alga Synedra acus from Lake Baikal

Abstract: Complete chloroplast genome of diatom alga Synedra acus possesses canonical quadripartite structure with two inverted repeats containing ribosomal RNA gene loci that separate small and large single-copy regions. Chloroplast genome maps as a circular molecule of 116 251 bp. It encodes 27 tRNAs, three rRNAs, two small RNA genes, and 128 protein-coding genes. Comparison of the genic features across diatom chloroplast genomes reveals the absence of an overlap between atpD and atpF gene coding sequences that is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The S. horneri cpDNA contains 16 SIRs and 9 TRs (Table 2), representing 1.02 and 0.32 % of the S. horneri genome, respectively, which is similar to those of three other brown algal cpDNAs. The total repeat number found in brown algal cpDNAs (18-25) is similar to that in diatoms (Oudot-Le Secq et al 2007;Galachyants et al 2012), more than that in Pelagophyceae (Ong et al 2010), and less than that in Raphidophyceae (Cattolico et al 2008).…”
Section: Small Inverted and Tandem Repeatsmentioning
confidence: 88%
See 1 more Smart Citation
“…The S. horneri cpDNA contains 16 SIRs and 9 TRs (Table 2), representing 1.02 and 0.32 % of the S. horneri genome, respectively, which is similar to those of three other brown algal cpDNAs. The total repeat number found in brown algal cpDNAs (18-25) is similar to that in diatoms (Oudot-Le Secq et al 2007;Galachyants et al 2012), more than that in Pelagophyceae (Ong et al 2010), and less than that in Raphidophyceae (Cattolico et al 2008).…”
Section: Small Inverted and Tandem Repeatsmentioning
confidence: 88%
“…The overlaps of psbC-psbD (53 bp) and rpl23-rpl4 (8 bp) are highly conserved among the four brown algal cpDNAs. These two overlapping regions are also observed in diatom plastid genomes (e.g., Oudot-Le Secq et al 2007;Tanaka et al 2011;Galachyants et al 2012).…”
Section: Genome Featuresmentioning
confidence: 92%
“…To date, a few dozen diatom chloroplast genomes (plastomes) have been sequenced (Kowallik et al 1995, Oudot-Le Secq et al 2007, Tanaka et al 2011, Galachyants et al 2012, Brembu et al 2014, Ruck et al 2014, Yu et al 2018. They are circular chromosomes with a quadripartite structure and two inverted repeats (IR) separating small (SSC) and large singlecopy (LSC) regions.…”
mentioning
confidence: 99%
“…from Lake Baikal. First, we deciphered mitochondrial [4] and chloro plast [5] genome sequences of Synedra acus subsp. radians in collaboration with the Center "Bioengi neering," Russian Academy of Sciences.…”
mentioning
confidence: 99%
“…radians via horizontal gene transfer and a region of diatom mtDNAs with intensive gene rearrangements as opposed to the rest of mitochondrial DNA sequence where the order of genes is conserved [4]. It was shown that the gene order in chloroplast DNA could be used for phyloge netic analysis [5].…”
mentioning
confidence: 99%